A nonlinear Klein–Gordon equation on a star graph. Issue 9 (24th August 2021) - Goloshchapova, Nataliia
Abstract: We study local well‐posedness and orbital stability/instability of standing waves for a first order system associated with a nonlinear Klein–Gordon equation on a star graph. The proof of the well‐posedness uses a classical fixed point argument and the Hille–Yosida theorem. Stability study relies on the linearization approach and recent results for the NLS equation with the δ‐interaction on a star graph.